The Relationship Between Workload and Motivation with Nurses' Turnover Intention at Gladish Medical Center Hospital - Tri Sundari; Yunina Elasari (INDOGENIUS, 2026)
Background & Objective: Turnover is a problem that occurs both globally and nationally. In 2020, the nurse turnover rate reached 19.5%. Several countries have also reported high levels of turnover intention, including Belgium (30%), Finland (49%), Germany (36%), Ireland (44%), the Netherlands (19%), Norway (25%), Poland (44%), Spain (27%), Switzerland (28%), and the United Kingdom (44%). Workload and work motivation are known to influence turnover intention. This study aimed to determine the relationship between workload and motivation with turnover intention among nurses at Gladish Medical Center General Hospital. Method: This quantitative research used a cross-sectional design with a total sample of 41 nurses, conducted in August 2025. Bivariate analysis was performed using the Gamma test. Result: The univariate results showed that turnover intention was mostly in the moderate category (80.5%), workload in the moderate category (85.4%), and work motivation in the moderate category (61.0%). The bivariate analysis showed a significant relationship between workload and turnover intention (p-value = 0.011) and between work motivation and turnover intention (p-value = 0.009). Conclusion: It is recommended that hospital management adjust job descriptions and task allocation to remain within reasonable limits to reduce the risk of turnover intention among nurses.